2014
DOI: 10.4161/15384101.2015.945823
|View full text |Cite
|
Sign up to set email alerts
|

CD151 represses mammary gland development by maintaining the niches of progenitor cells

Abstract: Tetraspanin CD151 interacts with laminin-binding integrins (i.e., a3b1, a6b1 and a6b4) and other cell surface molecules to control diverse cellular and physiological processes, ranging from cell adhesion, migration and survival to tissue architecture and homeostasis. Here, we report a novel role of CD151 in maintaining the branching morphogenesis and activity of progenitor cells during the pubertal development of mammary glands. In contrast to the disruption of laminin-binding integrins, CD151 removal in mice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 68 publications
5
10
0
Order By: Relevance
“…These findings demonstrate a strong mechanistic link between CD151 expression and GSC stemness and provide a novel functional context to our recent report showing that CD151 resides within a transcriptional network that is repressed by KLF9, a transcription factor that induces GSC differentiation and inhibits GSC tumor-propagating potential. Our data extend and provide a functional context to previous studies from other investigators in different organ systems showing an association of CD151 expression with the capacity of prostate cancer cells to self-renew as spheres [39] and the CD151-dependent regulation of progenitor cell pools during mammary development [58] .…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…These findings demonstrate a strong mechanistic link between CD151 expression and GSC stemness and provide a novel functional context to our recent report showing that CD151 resides within a transcriptional network that is repressed by KLF9, a transcription factor that induces GSC differentiation and inhibits GSC tumor-propagating potential. Our data extend and provide a functional context to previous studies from other investigators in different organ systems showing an association of CD151 expression with the capacity of prostate cancer cells to self-renew as spheres [39] and the CD151-dependent regulation of progenitor cell pools during mammary development [58] .…”
Section: Discussionsupporting
confidence: 85%
“…A role for CD151 in regulating cell stemness and cancer stem cells remains undefined. Yin et al [58] found that CD151 knockout increased the differentiation potential of mammary luminal stem and progenitor cell subtypes, suggesting a role in modulating mammary cell multipotency and differentiation signals. We recently reported a potentially related finding that CD151 is among a network of genes that are repressed by KLF9, a transcription factor that drives GSC differentiation [27] , [59] .…”
Section: Introductionmentioning
confidence: 99%
“…5b ). To corroborate these findings, we also used a second set of breast CSC markers (CD49f high /CD24 low ) 39 40 41 42 . Similar to the results presented above, Dub3 knockdown reduced the population of CD49f high /CD24 low cells in MDA-MB231 and MDA-MB157 cells (lower panel in Fig.…”
Section: Resultsmentioning
confidence: 95%
“…Of note, CD151 may also drive glioblastoma malignancy by affecting the stemness property of glioma cells. This tetraspanin has recently been linked to the dynamics of tumor-initiating or progenitors cells [ 43 , 44 ]. Also, CD151-associated α3 and α6 integrins are shown to enhance the aggressive behaviors of cancer stem cells [ 7 , 10 ].…”
Section: Discussionmentioning
confidence: 99%